2008 IEEE Sensors 2008
DOI: 10.1109/icsens.2008.4716530
|View full text |Cite
|
Sign up to set email alerts
|

Development of a complete dual-axis micromachined convective accelerometer with high sensitivity

Abstract: A convective accelerometer is an accelerometer, which contains neither a solid proof mass nor moving components. It mainly consists of heaters and thermal sensors which measure temperature differences caused by free convection due to an input acceleration. In this paper, we report a complete dual-axis micromachined convective accelerometer with high sensitivity and an effective microfabrication process to realize the device. Compared with other convective accelerometers, our design shows dramatically increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Sensitivity of a thermal accelerometer depends on the size and shape of the heater structure. Four types of heater structures were compared (in [40], [16]) and it was shown that a diamond-shaped heater (shown in figure 5) provided higher temperature gradient at the temperature sensing point in comparison to a square-shaped heater. The diamond-shaped heater was further modified by using high resistive material at the corners due to which the temperature gradient at the sensor To improve the bandwidth of thermal accelerometers, the cavity size should be made small and thermal diffusivity of the working fluid must be high.…”
Section: 1: Thermal Accelerometer In Mems Processmentioning
confidence: 99%
“…Sensitivity of a thermal accelerometer depends on the size and shape of the heater structure. Four types of heater structures were compared (in [40], [16]) and it was shown that a diamond-shaped heater (shown in figure 5) provided higher temperature gradient at the temperature sensing point in comparison to a square-shaped heater. The diamond-shaped heater was further modified by using high resistive material at the corners due to which the temperature gradient at the sensor To improve the bandwidth of thermal accelerometers, the cavity size should be made small and thermal diffusivity of the working fluid must be high.…”
Section: 1: Thermal Accelerometer In Mems Processmentioning
confidence: 99%
“…Since then, many studies have been conducted on these sensors. Most of the studies have focused on improving the sensor performance by optimizing the fluid medium with proper thermal properties (e.g., thermal conductivity, thermal diffusivity, kinematic viscosity), temperature sensing (e.g., thermal couple, thermistor), the material of the thermistor (e.g., metal thermistor, polysilicon thermistor, silicon PN junction thermistor) and the structure of the sensor (e.g., cavity shape and size, cap shape and size, distribution and size of the heater and thermistors) [ 6 , 7 , 8 , 9 , 10 , 11 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 ]. Combinations of Finite-Element-Modeling (FEM) simulation and experimental validation are the most commonly-used research methods.…”
Section: Introductionmentioning
confidence: 99%
“…The magnitude of the applied acceleration is output as an electric impulse, later processed to evaluate acceleration, inclination, rotation, vibration, shocks, tilt angle, inertial motion, etc [2][3][4]. Some examples of successful transduction mechanisms used in accelerometers are piezoelectric, piezoresistive, capacitive, resonant frequency shift, and thermal sensing devices [1,[4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Thermal accelerometers use a transduction mechanism based on air convection. This type of sensor differs from the traditional mechanical accelerometers mainly due to the absence of a proof-mass, simplifying the fabrication process while improving reliability [2,[5][6][7]. The conventional design has a cavity etched on silicon, hermetically sealed to prevent external influences from disturbing the device operation.…”
Section: Introductionmentioning
confidence: 99%